2010
DOI: 10.1017/s0950268810002402
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of hospitalized patients with bacteraemic and non-bacteraemic community-acquired pneumonia caused by Streptococcus pneumoniae

Abstract: In contrast to bacteraemic pneumococcal community-acquired pneumonia (CAP), there is a paucity of data on the clinical characteristics and outcomes of non-bacteraemic pneumococcal CAP. This retrospective study compared the outcome of hospitalized patients with bacteraemic and non-bacteraemic pneumococcal CAP treated at a medical centre from 2004 to 2008. Data on clinical outcomes including all-cause mortality, length of hospital stay, need for intensive-care unit admission and extrapulmonary involvement were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
4
22
1
Order By: Relevance
“…Kaplan-Meier curve for length of stay among 439 non-bacteremic and 394 bacteremic patients with S. pneumoniae community-acquired pneumonia The results of our study contradict prior reports suggesting no association of bacteremic pneumococcal CAP and poor outcomes [13,14]. However, other investigators have found that bacteremia is a risk factor for death in patients with pneumococcal CAP [6][7][8][9][10][11]. In a prospective study carried in two hospitals in northern Spain (2001-2009), Capelastegui et al compared 492 non-bacteremic pneumococcal CAP patients with 399 bacteremic pneumococcal CAP [10].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Kaplan-Meier curve for length of stay among 439 non-bacteremic and 394 bacteremic patients with S. pneumoniae community-acquired pneumonia The results of our study contradict prior reports suggesting no association of bacteremic pneumococcal CAP and poor outcomes [13,14]. However, other investigators have found that bacteremia is a risk factor for death in patients with pneumococcal CAP [6][7][8][9][10][11]. In a prospective study carried in two hospitals in northern Spain (2001-2009), Capelastegui et al compared 492 non-bacteremic pneumococcal CAP patients with 399 bacteremic pneumococcal CAP [10].…”
Section: Discussioncontrasting
confidence: 71%
“…Despite these interventions, S. pneumoniae remains the most common cause of CAP, of which 20 % of cases are accompanied with bacteremia [5]. Controversy still exists regarding the impact of bacteremia on the clinical outcomes of hospitalized patients with pneumococcal CAP [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The previous South African study documented an overall mortality of 20%, this being 28.5% in those given guideline-adherent therapy, and 19% in those given guideline-nonadherent therapy, which was not significantly different; p = 0.71) [7]. The reasons for the differences in mortality between these two studies is uncertain but may relate to the fact that the earlier study was restricted to the investigation only of severely ill cases with CAP, and also that microorganisms were isolated in a significantly greater number of the cases (although the site of isolation was not reported) and CAP cases that are more severe [9], as well as those that have documented bacteraemia are known to have a poorer prognosis [16]. An additional reason that non-adherent therapy was not associated with a higher mortality in either of the studies may relate to the fact that in both studies, those patients that received non-adherent therapy, had not received, in most cases, inadequate therapy, but had received antibiotic therapy in excess of what was recommended [7].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence suggesting that infections by some organisms, such as Streptococcus pneumoniae, are linked to higher rates of bacteremia [10], which was proposed to explain higher mortality rates from pneumococcal pneumonia in these patients [9]. However, this conclusion is not unequivocally accepted, as other reports did not find higher rates of bacteremia in diabetic patients with pneumococcal pneumonia [11]. In addition, a recent report from the Community-Acquired Pneumonia Organization international cohort study not only disclosed that pneumococcal bacteremia did not impact the outcome, they moreover reported that people with diabetes mellitus were more likely to achieve clinical stability and that diabetes was not a risk factor for death when suffering from bacteremic pneumococcal infection [12].…”
Section: Diabetes and Infection Susceptibilitymentioning
confidence: 99%